Cold storage of Trichogramma nerudai using an acclimation period - Cagnotti, Cynthia Lorena (2018)
The availability of suitable storage methods for parasitoids is a valuable tool in biological control programs. Studies were conducted to investigate the effects of cold storage with acclimation period on the quality of Trichogramma nerudai Pintureau and Gerding. Prepupae were stored 50, 75 and 100 days at 5 °C with a previous acclimation period of 10 or 20 days at 12 °C. It was possible to arrest the development of T. nerudai. All the treatments with acclimation period of ten days had emergence values under 10% that were not useful to establish a cold storage protocol. Twenty days of acclimation had a positive impact on cold storage tolerance at 50 and 75 days. The adult emergence, the emergence time, the sex ratio, the parasitism and the progeny quality have not been affected by the storage of T. nerudai using an acclimation period of 20 days and until 50 days under cold temperature.